Generation Z’s Attitudes towards the Work Environment on the Example of Working Students in Poland and Croatia – a Comparative Analysis - Kawka, Tomasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: To interpret preliminary pilot studies diagnosing the attitudes of Generation Z towards work conditions in Poland and Croatia. It uses the example of a selected group of working students in the two countries. The level and attributes of professional satisfaction, the assessment of commitment, and selected components of the assessment of one’s work environment were the determinants of the individuals’ attitudes. Research Design & Methods: Comparative research was carried out using a modified P.A.S.Z. questionnaire. The first section characterises the group of Generation Z employees, who were beginning to work. The next section examines the results of the research and discusses the similarities and differences in the expectations young Poles and Croats have of work towards the work. The group surveyed was made up of individuals finishing their university education and beginning their first stage of development and gaining professional experience. Against this background, fundamental questions and research hypotheses were verified. This constitutes the basis for the further stages of comparative research on the subject. Findings: The research shows that working students appreciate their work environment as one characterised by a high level of professional satisfaction. Working students in Poland and Croatia show an identical structure of values and motives for taking up work, both leading to job satisfaction. Implications / Recommendations: Despite their cultural differences and different nationalities, the Polish and Croatian representatives of Generation Z had very similar results in terms of their expectations and attitudes. Thus, an assumption can be made about a global, homogeneous perception of one’s professional role by the youngest generation entering the labour market in the sample of students. Contribution: The study confirms the characteristics of Generation Z as a homogeneous and global generation in terms of how they perceive their work environment.